(untitled) (Conference on English Language Teaching, 2023)
The aim of this study is to identify the kinds of associative meaning used by Najwa Shihab Chris Martin of Coldplay employed in exclusive interview. This study used a descriptive qualitative research approach in analysing the associative meanings This research uses the theory conducted by Leech to find out the types of associative meaning those are connotative meaning, social meaning, affective meaning, reflected meaning, and collocative meaning. After collecting the data, the researchers used some steps proposed by Berg to analyze the data. The researchers classified words, phrases or sentences that contained associative meaning The result shows that the types of associative meaning appeared in this research. Those are connotative meaning (9 data), social meaning (1 data), affective meaning (21 data), reflective meaning (2 data), and collocative meaning (5 data). Based on the data, this indicated that the the conversation are dominantly have affective meaning. The majority of the sentence that they utter were about revealed how excited they were for the event that would take place in Indonesia on November 2023, reactions to the songs and the concert’s theme, as well as the fans’ desire to interact with one another especially with the band.